Symposium on market microstructure: Focus on Nasdaq - Schwert, G.William (Journal of Financial Economics, 1997)
This special issue of the Journal of Financial Economics includes six articles that analyze the market microstructure of Nasdaq in various ways. The question of the costs of trading on Nasdaq has become contentious in both the academic and legal/regulatory arenas since the Christie and Schultz (1994) article first noted that many actively traded Nasdaq stocks were almost never quoted on odd eights. The articles in this symposium bring new and interesting insights to this debate.